THE EFFECT OF INSTANT BREAD YEAST AND CARRAGINAN CONCENTRATION ON THE QUALITY OF SORGUM FLOUR SUBSTITUTED BREAD: The Effect Of Instant Bread Yeast And Carraginan Concentration On The Quality Of Sorgum Flour Substituted Bread - Baiq Candra Puspitasari; Sri Widyastuti; moegiratul amaro (Pro Food, 2023)
The aimed of this research was to know the effect of concentrations of instant bread yeast and carrageenan on the quality of sorghum flour-substituted white bread. Theresearch methode used was an experimental method with factorial Completely Randomized Design (CRD), consiting of concenttration of yeast (2%, 4%, and 6%) and Carrageenan (0%, 0.2%). Observational data were analyzed using analysis of variance with a level of 5% using Cos-Stat, if there significantly differen data a further test was carried out usinh Honest Significant Different (BSD) at the 5% level. Parameters observed included chemical quality (fiber content, ash content, and content), physical quality (swelling power, elasticity, and bread crumbs), and organoleptic quality (aroma, taste, texture, crust color, and crumb color). The results showed that yeast formulation with at 4% and carrageenan 0.2% was the best treatment in producing white bread with a moisture content of 23.72% (according to SNI), ash content of 1.9%, crude fiber content of 5.33%, 67.83% swelling power by reducing the size of the pores so as to create uniform bread pores, 84.44% elasticity with organoleptic crust color "light brown", aroma "slightly sour", taste "not sour", texture "a bit soft" and the crumb color "yellowish white" which was liked by the panelists. The best quality bread in this study was bread treatment R2K2 with the addition of instant bread yeast and carrageenan of 4% : 0,2%, based on the result of pysicalchemical, and organoleptic with the best results.